HĒ ALĒTHEIA ELEUTHERŌSEI: SEBUAH PEDEKATAN EKSEGETIS TERHADAP INJIL YOHANES 8:31-32 - Zulkifli Oddeng (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
The essence of truth in the general conception is always depends on the value of objectivity, coherence, or utility. Specifically in Christianity, truth – which is called Alētheia – is not tied to these values, but is found in Jesus Christ himself. An exegetical approach to the text of the Gospel of John 8:31-32 describes the concept of the liberating Alētheia, namely the condition that is equated with knowing the truth and becoming a disciple of Jesus when someone remains in Jesus and His word. By placing the issue of sin as a crucial context, this liberating concept of truth also triggers a rethinking of the idea of cosmic Christology, especially that proposed by Joas Adiprasetya, who proposed the possibility of actualizing the Alētheia in non-Christian religions.